A comprehensive structural and functional analysis of the ligand binding domain of the nuclear receptor superfamily reveals highly conserved signaling motifs and two distinct canonical forms through evolution. (2019) - MITSIS, THANASIS; PAPAGEORGIOU, LOUIS; EFTHIMIADOU, ASPASIA; BACOPOULOU, FLORA; VLACHAKIS, DIMITRIOS; CHROUSOS, GEORGE P.
No abstract available